2021
DOI: 10.32098/mltj.01.2021.15
|View full text |Cite
|
Sign up to set email alerts
|

Core Muscles Endurance in Sedentary Individuals with and without Nonspecific Chronic Low Back: A Cross-Sectional Study

Abstract: Background. Musculoskeletal dysfunction is one of the most important occupational health issues. Prolonged sitting may be a risk factor for low back pain (LBP) associated with reduced muscle endurance, although many people with a sedentary lifestyle and sitting-type job report no pain and discomfort in the lumbar region. In the present study, endurance of the core muscles in individuals with sedentary jobs with nonspecific chronic LBP were compared with those without LBP. Objective. The present study compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 87 publications
(129 reference statements)
0
2
0
Order By: Relevance
“…This may be due to the high physical requirements of manual handling tasks. In contrast, Esfahani et al (47) concluded that their findings do not support the prevailing view that prolonged sitting at work as part of everyday life is necessarily associated with LB pain; rather, sitting posture, lower levels of physical fitness, and shorter duration of home activities may be associated with reduced extensor endurance in nonspecific chronic LB pain. In this survey, most nurses (65% male and 57% female) were within the normal weight range and their BMI was unrelated to MSDs.…”
Section: Discussionmentioning
confidence: 84%
“…This may be due to the high physical requirements of manual handling tasks. In contrast, Esfahani et al (47) concluded that their findings do not support the prevailing view that prolonged sitting at work as part of everyday life is necessarily associated with LB pain; rather, sitting posture, lower levels of physical fitness, and shorter duration of home activities may be associated with reduced extensor endurance in nonspecific chronic LB pain. In this survey, most nurses (65% male and 57% female) were within the normal weight range and their BMI was unrelated to MSDs.…”
Section: Discussionmentioning
confidence: 84%
“…Some studies showed the association between head position and shoulder posture (29,33,(35)(36)(37). Haddadi et al (38) also reported that a slump sitting position may be associated with reduced extensor muscle endurance in nonspecific chronic low back pain (38) so interestingly, the future study needs to investigate the effect of the LCS type B with nonspecific chronic low back pain on upper body postures while sitting. For trunk flexion angle, this study found that people with the LCS type B had less trunk flexion angle than healthy people and those with LCS type A significantly, possibly due to tightness of the upper abdominal muscles, as well as greater stretching of back extensor muscles results in kyphosis of thoracic spine and a decrease in lumbar lordosis, so, people with the LCS type B had bending posture more than healthy groups and people with LCS type A (14,15).…”
Section: Discussionmentioning
confidence: 96%